Stock Estimation and Carbon Absorption of Mangrove in Tallo River, Makassar - Rahman Rahman; Hefni Effendi; Iman Rusmana (Jurnal Ilmu Kehutanan)
The mangrove ecosystem has a higher ability of CO2 absorption than other vegetations. However, the effort to establish the mangrove to be a carbon stock area has not been achieved. Makassar has Tallo River, covered with mangrove vegetation along its riverbank, which is potent to be managed as a green open space. The observations indicated that Tallo River was located in the center part of Makassar city and was dominated by Nypa fruticans along the riverbanks in 18,514 trees and a density of 4,256 trees/ha, stored carbon of 21.82 tons C/ha, and absorbs 80.02 tons CO2/ha. Rhizophora mucronata was the second dominant species in 8.492 trees and density of 2,352 trees/ha, stored carbon of 19.94 tons C/ha, and absorbs 73.13 tons CO2/ha. The third dominant species was Avicennia alba in 2,421 trees and density of 3,228 trees/ha, stored carbon of 263.85 tons C/ha, and absorbs 197.89 tons CO2/ha. The density and ability to absorb values of the mangrove is highly suitable to be managed for a green open space to supply fresh air and CO2.